Exacerbating Guillain–Barré Syndrome Eight Days after Vector-Based COVID-19 Vaccination - Josef Finsterer (Case Reports in Infectious Diseases)
Since the introduction of mRNA technology-based and vector-based COVID-19 vaccines, adverse reactions to these agents have been occasionally reported. Exacerbation of Guillain–Barré syndrome (GBS) shortly after COVID-19 vaccination has not been communicated. The patient is a 32-year-old male who developed progressive sensory disturbances and muscle weakness 8 days after the first dosage of a vector-based vaccine. Cerebrospinal fluid investigations revealed a dissociation cyto-albuminque, and nerve conduction studies revealed demyelination. Intravenous immunoglobulin (IVIG) exhibited only a marginal effect for both sensory and motor deficits. The patient’s history was moreover positive for previous GBS with marked motor deficits 14 years earlier, which responded favourably to IVIG leading to almost complete recovery within 9 months of rehabilitation. Although apparently extremely rare, neurologists should remain vigilant for a potential recurrence of GBS after vaccination with a vector-based COVID-19 vaccine.